Standard Precautions Are The Work Practices Required To Achieve A Basic Level Of Infection Prevention And Control (The Review of Diabetic Studies, 2024)
Healthcare-associated infections cost the Ministry of health millions annually. Each infection costs additional money and resources. They also make patients unsafe and uncomfortable. Healthcare professionals (HCPs) are returning to handwashing as healthcare-associated infections (HCAIs) become more widespread, illnesses more serious, and treatments more complicated. However, healthcare personnel' hand hygiene compliance has continually been low. Two weeks of prospective observational data were collected on employees' basic hand hygiene routines. Two weeks were spent collecting prospective observation data. 217 times, various groups of employees appeared at different times. All nurses, ANPs, and domestic workers were bare below the elbow, but just 37% of consultants were. Consultants rubbed their hands 37% before and 33% after. ANPs did best, utilizing alcohol hand rub before and after patient contacts 70% of the time. Healthcare providers must be ready to teach patients how to wash their hands, a simple yet useful habit. This study demonstrates the standard was partially met.